MANAJEMEN KESANTUNAN BERBAHASA DALAM PEMBELAJARAN BAHASA INGGRIS DI SEKOLAH (Penelitian Pada PBM Bahasa Inggris di kelas X MIPA-3 SMAN 27 Bandung) - Muhammad Hasan Basari; Sofyan Sauri (LPPM Institut Agama Islam Ibrahimy Genteng Banyuwangi, 2021)
Language politeness management is a conversation that is used by someone to others as opposed to speaking with subtle language, good, calm and polite so that it can be a manifestation of the modesty of his behavior in accordance with the norms and values ​​adopted and held by the community where he lives through the management function of William A Shcrode and Dan Voice, Jr., which includes: planning, implementing, and evaluating. This research uses descriptive-qualitative method with the subject of educators and students and the object of the English language teaching and learning process in class X- Sciences-5 of 27 public senior high school. Through tapping techniques, competent listening, recording techniques and note taking techniques. By adhering to the principle of politeness in the maxim of wisdom, maxim of generosity, maxim of simplicity, maxim of agreement, appreciation and maxim of sympathy. This study aims to describe the politeness of language in learning English which is managed through planning, implementation and evaluation. The results of this study indicate that the politeness of language in learning English in class X-Sciences-5 of 27 public senior high school has been made planning, implementation and evaluation but not entirely optimal.